DEVELOPMENT OF SIMULATION-BASED 3D EDUCATIONAL REPLICA MEDIA TO IMPROVE STUDENTS' PSYCHOMOTORIC ABILITIES IN FIQIH MATERIAL IN CLASS VII AT MTs SYIAR ISLAM MAIBIT - Dewi Purwani; Moh. Mundzir (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
The low psychomotor abilities of students in Fiqh learning at MTs Syiar Islam Maibit are caused by the dominant use of lecture methods and the lack of concrete, innovative, and interactive learning media. This condition results in students being less active in understanding and practicing worship materials, especially prayer materials in various situations. This study aims to produce a valid, practical, and effective simulation-based 3D educational replica media in improving the psychomotor abilities of seventh-grade students on prayer materials in various situations. This study uses the Research and Development (R&D) method with a 4D development model that includes the define, design, develop, and disseminate stages. The validation process is carried out by material experts and media experts to determine the level of product feasibility, while the practicality of the media is measured through teacher and student response questionnaires. The effectiveness of the media is analyzed using observation sheets of students' psychomotor abilities before and after using the media with N-Gain calculations. The results of the study showed that the level of media validity was very high, with a percentage of validation from material experts of 96%, media experts of 98.57%, and teacher responses of 96.67%, all of which were in the very valid and very suitable category for use. In addition, student responses to the practicality of the media reached 91.88% with a very practical category. The use of the media was also proven to be effective in improving students' psychomotor abilities, indicated by an increase in observation scores from an average of 66.00% to 95.00%, as well as an average N-Gain value of 0.85 which was included in the high category. Thus, the simulation-based 3D educational replica media was declared suitable, practical, and effective for use in Fiqh learning.